IMPLEMENTATION OF ISLAMIC BUSINESS ETHICS ON SMALL AND MEDIUM-SIZED ENTERPRISES (SMEs): CASE STUDY OF SMEs XYZ - Oktarina, Amimah; Mu'alim, Amir (Universitas Muhammadiyah Yogyakarta, 2017)
The rapid growth of Small and Medium-sized Enterprises sector(SMEs) in Indonesia increases business competition become strict and complicate among them. Competition of existing businesses tends to be unhealthy and ignore the ethical values. It makes the discourse of business ethics at SMEs is indispensable in order to form the basis for operations and avoid deviations ethical values. As a manufacturer of fish processing has been certified halal by the MUI,SMEs XYZ should be able to apply Islamic business ethics in its activities. So it is not only profit oriented, but also pay attention to ethical values. This study aimed to describe the implementation of Islamic business ethics which consists of four (4) axiomswhich areunity, equilibrium, free will, and responsibility in SMEs XYZ. The method used in this research is descriptive qualitative analysis through the 4 (four) stages of data collection, data reduction, data display, and conclusion. The result in this study is SMEs XYZ was implemented Islamic business ethics on its operations.